Assessing We-Disease Appraisals of Health Problems: Development and Validation of the We-Disease Questionnaire - Alexandra J. Vogt; Lasse Bartels; Isabella C. Bertschi; Fiona Mahler; Michael Grotzer; Daniel Konrad; Kurt Leibundgut; Jochen Rössler; Guy Bodenmann; Markus A. Landolt (MDPI AG, 2024)
In couples dealing with health problems, we-disease appraisals can influence dyadic coping strategies to alleviate distress. This study describes the development and validation of a self-report scale to assess we-disease appraisals of health problems. The newly developed We-Disease Questionnaire (WDQ) was administered in three samples: parents of children with type 1 diabetes (n = 240) or cancer (n = 125) and individuals with visual impairment and their partners (n = 216). Reliability was measured by coefficient omega. To assess construct validity, correlations with other measures of individual and dyadic adjustment were examined. Descriptive statistics across all samples were compared. A 4-item version of the WDQ demonstrated good reliability and validity and showed meaningful associations with established scales. We-disease appraisals were highest among parents of children with cancer and lowest among couples with visual impairment. The WDQ is a reliable and valid measure that can be used across different health problems.